2022
DOI: 10.1002/aenm.202202820
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Stabilized Organic Nanoparticle Dispersions for the Fabrication of 10% Efficient Non‐Fullerene Solar Cells

Abstract: An entirely different route to the ecofriendly processing of organic semiconductor thin films is their deposition from aqueous or alcoholic dispersions, [4] reinforcing the unique environmental sustainability of organic solar cells. Recent reports also featured acetonitrile as a promising dispersion agent due to its high permittivity and hence its excellent screening of stabilizing charges. [5] Besides the omission of toxic solvents during coating, this deposition route i) disentangles solution processing from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 51 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…55 High efficiency OPV devices have been achieved with nanoparticles presenting intermixed morphology, generally obtained from the nanopre- cipitation method, but also the miniemulsion method in several cases. 8,13,56,57 One can highlight the 7.5% PCE achieved for the PBQ-QF:ITIC system 8 from water-based dispersions and 4.3% for P3HT:ICBA 58 from alcohol-based dispersions. It has been shown in several studies by the Venkataraman group 59,60 that, if the surfactant is efficiently removed, the charge transport in OPV devices is not drastically affected and it is comparable to thin films deposited from organic solvents.…”
Section: Connection Of Structure To Functionmentioning
confidence: 97%
“…55 High efficiency OPV devices have been achieved with nanoparticles presenting intermixed morphology, generally obtained from the nanopre- cipitation method, but also the miniemulsion method in several cases. 8,13,56,57 One can highlight the 7.5% PCE achieved for the PBQ-QF:ITIC system 8 from water-based dispersions and 4.3% for P3HT:ICBA 58 from alcohol-based dispersions. It has been shown in several studies by the Venkataraman group 59,60 that, if the surfactant is efficiently removed, the charge transport in OPV devices is not drastically affected and it is comparable to thin films deposited from organic solvents.…”
Section: Connection Of Structure To Functionmentioning
confidence: 97%
“…Achieving high performance requires careful consideration of all these factors. [82][83][84][85][86][87][88][89][90][91][92][93][94][95] Numerous studies have been conducted on the BHJ systems of P3HT:PCBM or P3HT:ICBA, demonstrating that surfactant-free nanoparticles can lead to PCEs of around 4% in OSCs [84] However, it has been observed that other "donor-acceptor" conjugated polymers and non-fullerene acceptors cannot remain stable without surfactants, as they tend to become electrically charged and subsequently repel the nanoparticles. [96] While surfactants play a crucial role in the formation of stable nanoparticles, they also possess an insulating nature that can have negative effects on electronic properties.…”
Section: Water/alcohol-processed Oscs Based On Conjugated Nanoparticlesmentioning
confidence: 99%
“…15 It is worth mentioning that a few research teams have explored the use of media other than water, such as alcohols or acetonitrile. 16,17…”
Section: Introductionmentioning
confidence: 99%
“…15 It is worth mentioning that a few research teams have explored the use of media other than water, such as alcohols or acetonitrile. 16,17 Two preparation techniques are mainly used to produce aqueous dispersions: miniemulsion and nanoprecipitation. There are fundamental differences between the mechanisms of each technique, influencing nanoparticle formation.…”
Section: Introductionmentioning
confidence: 99%